Strategic Human Resource Development Model for Ground Instructors in Aircraft Maintenance Training Division Of Civil Aviation Training Center - Montreecharoen, Papaporn (CRRU Law, Political Science and Social Science Journal, 2023)
In this dissertation, the researcher examines (1) the conditions of the problems and the needs for human resource development of ground instructors, Aircraft Maintenance Training Division, Civil Aviation Training Center; constructs (2) a strategic human resource development model for the instructors under study; and (3) evaluates the constructed model. The research was conducted in three steps as follows. The survey was conducted for the opinions of24 Ground Instructors. Constructed a strategic human resource development model for the ground instructors under study using the Delphi technique for three rounds with eighteen experts. The instrument on the first round was an interview form for experts using the Delphi technique. Data were analyzed using the techniques of median, interquartile range, and content analysis. Evaluated the constructed model using the technique of focus group discussion. The results of the research were as follows: 1) Conditions, problems, and the need for a model in human resource development of ground instructors, namely the setting of the context about stakeholders and stakeholders in human resource development of ground instructors; to formulate policies, strategies, and implement strategies by creating an integration between development, education and training in accordance with 4 aspects: vision identity and in terms of qualifications of Ground Instructors in Aircraft Maintenance Training Division of Civil Aviation Training Center Standards of 7 Organizations and Assessment of Human Resource Development Strategies. The operation continues along with clarity. 2) The Strategic Human Resource Development Model of Ground Instructor consisted of three main components used in the Model Development as follows : Part 1 Dimensions in the Strategic Human Resource Development Model of Ground Instructors in Aircraft Maintenance Training Division of Civil Aviation Training Center has 4 aspects (1) vision dimension (2) identity dimension (3) identity dimension and (4) standard dimension of the 7 organizations of the Civil Aviation Training Center, part 2 missions in various fields to accelerate the strategic human resource development of Ground Instructors in Aircraft Maintenance Training Division of Civil Aviation Training Center is (1) textbook writing and academic articles (2) research, (3) academic services, (4) teaching, and (5) advisors. Part 3 Mechanisms used in the strategic human resource development of Ground Instructors in Aircraft Maintenance Training Division of Civil Aviation Training Center consists of: (1) Contextualization of stakeholders and stakeholders Human resource development, (2) the internal environment audit, (3) the strategy formulation of human resource development in line with the organization’s vision and goals, (4) the implementation of the human resource development strategy, and (5) ) the assessment of human resource development strategies and 3) the results of the evaluation of the strategic human resource development model of Ground Instructor According to the opinions of experts, it was found that the overall probability of the model was at a high level. ( =4.43, 4.11), respectively.